The Measurement of Marginal Propensity to Consume (MPC) Based on Indonesian,s Consumption Pattern for the Period 2000-2006 - Soemartini Soemartini (STATISTIKA: Forum Teori dan Aplikasi Statistika, 2007)
Consumption expenditure is the biggest component of Gross Domestic Product, which indicate acountry walfare. The objective of this paper is to estimate the Indonesian,s marginal propensity toconsume and it,s rate of change for the period of 2000-2006. The empirical models used in thispaper were based on the one developed by Dumairy (1995) on the correlation between consumptionand permanent income , inflation, Wilcox ( 1989 ) on the correlation between consumption changeand interest rate and employment, and Faini (1991) on the correlation between consumption changeand saving , money supply , interest rate , real exchange and inflation. The models were estimatedafter OLS assumptions. In the of period 2000-2006, MPC estimated is 0,686. It,s also revealed thatreal exchange rate and inflation level give a negative impact to the change of consumption , althoughpartially the real exchange rate and inflation level give the significant influence.